Weathering processes and natural radionuclides - Bonotto, Daniel Marcos [UNESP]; Jiménez-Rueda, Jairo Roberto [UNESP] (My University, 2011)
In managing our hydrological systems, increasing use is being made of information generated from studies held for understanding the controls on chemical weathering due to its importance in affecting the evolution of the Earth's surface, shaping landscapes, determining nutrient supply to ecosystems, and regulating global chemical cycles. A lot of recent studies have been realized to determine the parameters controlling the denudation, chemical weathering and physical erosion under different climatic conditions. In order to estimate chemical weathering fluxes affecting the drainage basins, models utilizing the Na, Ca, K, Mg and total dissolved load concentrations have been applied to obtain fractions coming from dissolved rocks, after corrections for river waters of the atmospheric inputs, dissolved solids from ion exchange sites in clays minerals, dissolved solids due to changes in biomass and anthropogenic inputs, among other factors. Since uranium is among the main elements contributing to natural terrestrial radioactivity, several descendants of the mass number (4n+2) 238U decay series have also been utilized in studies focusing weathered soil covers and hydrological resources in drainage basins. The 238U decay series finishes at the stable 206Pb and the radionuclides 238U and 234U have been used to evaluate the chemical weathering rate in soil profiles and hydrographic basins based on the fact that 234U is preferentially mobilized to 238U when rock weathers in the alteration front. Measurements of the 234U/238U activity ratio (AR) in rocks, soils and waters have allowed the calculation of the solution coefficient for the uranium characteristic of the region, that allows evaluate the time necessary to weather 1 m of rock under actual climatic conditions. This chapter summarizes some studies realized in a soil profile occurring at the giant Paraná sedimentary basin, Brazil, which have taken into account the presence of natural radionuclides belonging to the 238U decay series. © 2011 Nova Science Publishers, Inc.